UJI KONSENTRASI HORMON AUKSIN UNTUK MEMACU PERTUMBUHAN STEK BATANG PULAI GADING (Alstonia scholaris (L.)R. Br.) - Qori Amatun Nufus; M. Mardhiansyah; Viny Volcherina Darlis (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Alstonia scholaris is a high economic value, fast-growing species and spread widely. Alstonia scholaris used to overcome the problem of damage in mining fields. Besides that Alstonia scholaris is tolerant in various kinds of soil. Alstonia scholaris seeds was difficult to obtain is one of the constraints for large-scale planting. The propagation vegetatively or using the hormone of auxin help. The observations is to observe growth of Alstonia scholaris stem cutting increase speed growth of shoots, numbers of shoots, length growth of shoots and number of leaves. Used level of concentration were non-concentration (K0), 50 ppm (K1), 100 ppm (K2) and 150 ppm (K3). The results of study shows the best concentration at a concentration of 150 ppm (K3) with level of shoots growth is 0,42 day, average of shoots length is 0,36 cm and average number of Alstonia scholaris leaves is 4,30 pieces.Keywords: Alstonia scholaris, cutting, concentration, auxin hormone, growth